Identification of genes contributing to cisplatin resistance in osteosarcoma cells. Issue 1 (29th November 2022) - Xie, Mingzhong; Dai, Haoping; Gu, Qingwen; Xiao, Changming; Wang, Haozhong; Lei, Yang; Wu, Chunxiao; Li, Xuening; Lin, Birong; Li, Sen
Abstract : Osteosarcomas are prevalent in children and young adults and have a high recurrence rate. Cisplatin, doxorubicin, and methotrexate are common adjuvant chemotherapy drugs for treatment of osteosarcoma, but multidrug resistance is a growing problem. Therefore, understanding the molecular mechanisms of chemotherapy resistance in osteosarcoma cells is crucial for developing new therapeutic approaches and ultimately improving the prognosis of osteosarcoma patients. To identify genes associated with cisplatin resistance in osteosarcoma, we screened a large‐scale mutant library generated by transfecting human osteosarcoma cells with a piggyBac (PB) transposon‐based gene activation vector. Several candidate genes were identified by using Splinkerette‐PCR paired with Next Generation Sequencing. We created a disease‐free survival predictor model, which includes ZNF720, REEP3, CNNM2, and CGREF1, using TARGET (Therapeutically Applicable Research to Generate Effective Treatments) datasets. Additionally, the results of our enrichment analysis between the Four_genes_high group and Low_group suggested that these four genes may participate in cisplatin resistance in osteosarcoma through cross talk between various signaling pathways, especially the signaling pathway related to bone formation. These data may help guide future studies into chemotherapy for osteosarcoma. Abstract : To identify genes associated with cisplatin resistance in osteosarcoma, a large‐scale mutant library was generated and several candidate genes were identified by using Splinkerette‐PCR paired with next‐generation sequencing. Additionally, a disease‐free survival predictor model, which includes ZNF720, REEP3, CNNM2, and CGREF1 using TARGET (Therapeutically Applicable Research to Generate Effective Treatments) datasets were created.